KLASIFIKASI KARAKTERISTIK KONSUMEN SEPEDA MOTOR MERK T DI JAWA BARAT MENGGUNAKAN METODE NAÏVE BAYES CLASSIFIER PADA DATA MINING - Jaka Aulia Pratama; Zulhanif Zulhanif; Yadi Suprijadi (Jurnal Ilmiah Matematika dan Pendidikan Matematika (JMP), 2017)
PT. JKL has a role as a main dealer of T’s brand are handling three types of motorcycle products in West Java. These are type of Sport, CUB, and Scooter(Automatic Transmissions). The company records the buyer of T’s brand motorcycle in the Customer Database (CDB). CDB collected from 2011 to 2013 yielded information of consumer characteristics which is necessary in market planning. Consumer characteristics are classified into two groups: Repeated Order and New Customer. Classification methods used in the study of Data Mining is the Naïve Bayes Classifier. Model classification is done by calculating the conditional probability to choose the greatest value of probability. The accuracy of the classification is 83% and the error classification is 17%.